A Review of the Intrinsic Heavy Quark Content of the Nucleon - S. J. Brodsky; A. Kusina; F. Lyonnet; I. Schienbein; H. Spiesberger; R. Vogt (Advances in High Energy Physics)
We present a review of the state of the art of our understanding of the intrinsic charm and bottom content of the nucleon. We discuss theoretical calculations, constraints from global analyses, and collider observables sensitive to the intrinsic heavy quark distributions. A particular emphasis is put on the potential of a high energy and high luminosity fixed target experiment using the LHC beams (AFTER@LHC) to search for intrinsic charm.